2014
DOI: 10.1186/1756-0500-7-847
|View full text |Cite
|
Sign up to set email alerts
|

Using PhenX toolkit measures and other tools to assess urban/rural differences in health behaviors: recruitment methods and outcomes

Abstract: BackgroundThe overall study was designed to examine how vacation behavior affects rural and urban Minnesotans and North Dakotans. The purpose of this substudy was to describe the method for sampling, follow-up and response rate by gender and urban/rural location to help inform future studies in this population.MethodsEssentia health primary care patients (n = 1344) were sent a 21-page self-administered questionnaire. The questionnaire included questions on demographics, work history, perceived stress, work pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…For instance excessive tearing and itching of the eye; nasal itching and fullness; and head pain and throat clearing are all common manifestations when mucous membranes of the eyes, nose and/or the sinuses are exposed to chemical irritants. Literature shows that irritations of the eyes due to exposure to chemicals and particulate matter often manifest as excessive tearing with or without itching, while swelling or discharge, which were less often reported, is often related to infections of the eyes [ 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance excessive tearing and itching of the eye; nasal itching and fullness; and head pain and throat clearing are all common manifestations when mucous membranes of the eyes, nose and/or the sinuses are exposed to chemical irritants. Literature shows that irritations of the eyes due to exposure to chemicals and particulate matter often manifest as excessive tearing with or without itching, while swelling or discharge, which were less often reported, is often related to infections of the eyes [ 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Merhaj et al demonstrated similar findings when they reported that 97% of the respondents in a community within the vicinity of a cement factory suffered from eye irritations [ 20 ]. Additionally, nasal itching and fullness of the nostrils are often associated with allergic responses to specific, non-infectious particles such as plant pollens, dust mites, animal air, industrial chemicals and medicines, while nasal discharge is often due to infectious or foreign lodgment in the nasal cavity [ 18 , 19 ]. Furthermore, head pain and throat clearing have been demonstrated to be common manifestations of sinus irritation [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A PEI index score (0-10) is the sum of intervention steps each patient reports that the provider implemented. Tobacco use and socio-demographics (e.g., age, gender, race/ethnicity, rural/urban residence) were obtained using questions from the PhenX toolkit [31]. The PEI was administered at baseline collected reasons for tobacco treatment selection, past-7-day point prevalence of cigarette smoking, number of cigarettes per day, cigarette type, age of smoking onset, and cancer site and time since diagnosis.…”
Section: Patient Exit Interviews (Peis)mentioning
confidence: 99%
“…The moist sweetened tobacco (called Mo’assal) is placed in the head and is burned by lit charcoal. The mainstream smoke aerosol is produced when the smoker sucks through the hose via the mouthpiece [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since users require a waterpipe device to smoke, they usually smoke at their family or friends’ homes. In addition, they smoke in public sites where the device is available such as cafés (hooka bars), restaurants and picnic areas [ 5 ]. The device including the hose is usually used by multiple individuals and the only part that gets changed is the mouthpiece [ 3 ].…”
Section: Introductionmentioning
confidence: 99%